Kontroversi Hukum Islam Kontemporer (Kajian terhadap Aborsi di Bawah Kehamilan 4 Bulan) - Yusup, A. Markarma (State Institute of Islamic Studies (IAIN) Palu, 2015)
Discussing the controversy of contemporary Islamic law on abortion, especially under four months of pregnancy, it is always interesting to be discussed. Especially if it is associated with the medical science, the law enforcement and human rights. The law seems to be difficult to touch this matter, then it is compounded with suspected of hiding the practice of abortion in the name of health care. Regardless of the question of whether abortion do so on the basis of health considerations alone or indeed do so on the basis of other reasons, but nonetheless deaths from abortion is very worrying. Abortion was close relation to human rights on the one hand because every woman is entitled to her live a healthy reproductive life, but on the other side of the fetus in the mothers womb are also entitled to live and thrive. Two of these are reaping the benefit of debate among scholars. Some scholars allow and forbid others to submit their respective arguments